A V2O3-ordered mesoporous carbon composite with novel peroxidase-like activity towards the glucose colorimetric assay. Issue 27 (22nd June 2015) - Han, Lei; Zeng, Lingxing; Wei, Mingdeng; Li, Chang Ming; Liu, Aihua
Abstract : A V2 O3 -ordered mesoporous carbon composite (V2 O3 -OMC) exhibited excellent peroxidase-like activity, enabling the detection of glucose colorimetrically coupled with glucose oxidase. Abstract : It is of great scientific and practical significance to explore inorganic mimetic enzymes to replace natural enzymes due to their instability and high cost. Herein we present an interesting discovery that a V2 O3 -ordered mesoporous carbon composite (V2 O3 -OMC) has a novel peroxidase-like activity towards fast redox reaction of typical peroxidase substrates H2 O2 and 2, 2′-azino-bis(3-ethylbenzo-thiazoline-6-sulfonic acid) diammonium salt (ABTS). Due to the small size effect and large surface area of V2 O3 nanoparticles supported by OMC, V2 O3 -OMC exhibited excellent catalytic performance with a k cat of 1.28 × 10 4 s −1, K M (ABTS) of 0.067 mM and K M (H2 O2 ) of 0.16 mM, and a significantly higher catalytic efficiency ( k cat / K M ) towards the oxidation of ABTS in comparison with the natural peroxidases. Furthermore, the Ping-pong BiBi mechanism was proposed to explain the catalytic reaction by V2 O3 -OMC. Based on this highly active biomimetic peroxidase and the colorimetric detection of H2 O2, a facile analytical method was developed to detect glucose by using V2 O3 -OMC and glucose oxidase, which had a wide linear range (0.01–4 mM glucose), good selectivity and reliability for successful detection of various real samples. Thus, the novel V2 O3 -OMC peroxidase mimetic holds great promise for broad potential applications.